SERVICIOS DE ORIENTACIÓN SOCIOLABORAL EN LA REGIÓN DE MURCIA, ESPAÑA: BUENAS PRÁCTICAS Y DEBILIDADES - Sánchez-García, María Fe; García-García, María del Carmen; Suárez Ortega, Magdalena (Universidad de Costa Rica, 2019)
The socio-labor guidance services are a great support for the job-professional insertion of the job seekers. This research explores about the assessment that the different  elements that make up the good practices of orientation in the employment services of the Region of Murcia (Spain), based on the opinions of users and counselors. A  questionnaire was applied, performing a comparative analysis between intervening agents, in the framework of a survey study of a descriptive, inferential and correlational nature. Among the good practices perceived, the focus is on the user and their circumstances, while the shortcomings are mainly associated with the transparency of their methods and actions, and the accessibility of services. Also, in certain aspects  discrepancies are identified, withgenerally higher ratings among counselors.